Linkages between spatio‐temporal patterns of environmental factors and distribution of plant assemblages across a boreal peatland complex. (30th December 2015) - Graham, Jeremy A.; Hartsock, Jeremy A.; Vitt, Dale H.; Wieder, R. Kelman; Gibson, John J.
Abstract : Here we examine the arrangement of plant species across an oligotrophic bog/poor fen peatland complex in the North American boreal plain and the relationships of these species to their physical and chemical environment. A semi‐uniform spatial sampling approach was utilized to describe the species assemblages, pore‐water chemistry and physical condition of 100 plots throughout a single peatland complex. Regardless of sharing the same ground cover of Sphagnum mosses, the remaining species separated into four distinct assemblages, each with unique indicators. These species groups along with associated chemical and physical factors are organized into four ecosites: bog, margin (edge) and two poor fen ecosites. The plant assemblages of this peatland have a complex relationship with numerous gradients, both physical and chemical, including depth to water table, shade, pH, nutrient and base cation. Rather than being homogenous across the landscape, most environmental variables exhibit distinct spatial patterns and do so in relationship to the plant assemblages, forming spatially distinct ecosites across the complex. Base cation concentrations play a smaller role than previously thought in differentiating these ecosites, and in addition to shade and depth to water table, nitrogen in the form of dissolved organic nitrogen was highly related to the placement of these ecosites. Many significant chemical factors appear related to evaporative water loss within the peatland complex, and these chemical factors are used to differentiate the ecosites. However, the mediation of evaporative water loss is due largely to self‐generated responses of the plant assemblages related to shade through plant morphology and peat acrotelm development related to depth to water table. We conclude that plant species and associated environmental gradients act together to form spatially distinct ecosites. The distribution of these ecosites within this large, environmentally complex peatland is largely controlled by differing self‐generated responses along the hydrotopographical gradient of differential water loss.